A new libelluloid family from the Eocene Green River Formation (Colorado, USA) (Odonata, Anisoptera) - Zeiri, Asma; Nel, Andre; Garrouste, Romain (Zootaxa, 2015)
The new family Urolibellulidae is proposed for the new genus and species Urolibellula eocenica, based on a fossil dragonfly from the Eocene Green River Formation (USA). This new taxon is considered as the sister group of the extant Libellulidae. As the oldest libellulid dragonfly is dated from the Turonian, the Urolibellulidae should also be at least Late Cretaceous.